ASSURED‐compliant point‐of‐care diagnostics for the detection of human viral infections. (8th June 2021) - Naseri, Mahdi; Ziora, Zyta M; Simon, George P; Batchelor, Warren
Abstract: Viral disease outbreaks have been always a threat to global public health making affordable, rapid and accurate diagnostics highly important tools to slow down the spread of viruses and decrease the mortality rate. Point‐of‐care (POC) diagnostics have emerged as a strong tool for the diagnosis of viral infections, especially in countries where health‐care systems are inadequate to provide proper services to all citizens. According to the World Health Organization, an ideal POC diagnostic must be Affordable, Sensitive, Specific, User‐friendly, Rapid/Robust, Equipment‐free and Deliverable (ASSURED). This review surveys carefully each ASSURED criterion and identifies where existing viral POC diagnostics fail to meet these criteria. Given the widespread concern with plastic pollution, we also propose the addition of 'disposability' to the existing ASSURED criteria and consider the letter "D" as the representative of both Deliverable and Disposable. Next, the POC tests used for the diagnosis of several common human viral infections which met all the ASSURED criteria (ASSURED‐compliant) are described in detail. Finally, the future of ASSURED‐compliant POC diagnostics, capable of generating comparable results to the viral diagnostic gold standards, is discussed.